EFEKTIVITAS MODEL COOPERATIVE LEARNING TIPE TSTS DALAM MATERI OPERASI HIMPUNAN - Nida Farida; Yulis Jamiah; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe purpose of this research is to know and to describe the effectiveness of Cooperative Learning model of Two Stay  – Two Stray technique on set operation material in grade VII of SMPN 2 Pontianak. The researcher using pre-experimental method in the form of quantitative research. The participant of this research was 29 students of class VIIC SMPN 2 Pontianak. The result showed that the students learning mastery is achieved classically 86,67%. The student activity is 65,13% in the first meeting and  improved to 71,96% on the second meeting. The implementation of teachers class management is 3,42% in the first meeting and improved to 3,45% in the second meeting. On the other hand, students responds towards Cooperative Learning model of Two Stay – Two Stray technique is 82%. From the collected data, it can be concluded that Cooperative Learning model of Two Stay – Two Stray technique is effective to be applied on teaching set operation material on grade VII of SMPN 2 Pontianak.  Keywords: Cooperative Learning model of Two Stay – Two Stray, Learning Effectivity, Set Operation